PENGARUH PEREKRUTAN DAN TRAINING, PEMBERIAN TANGGUNG JAWAB, KOMPENSASI, DAN PROMOSI TERHADAP EFEKTIVITAS KINERJA KARYAWAN - Christine Herawati Limbong; Bhakti Helvi Rambe; Yudi Prayoga; Mulya Rafika; Dinda Karansita Hasibuan (Universitas Bina Taruna Gorontalo, 2020)
Patient satisfaction is influenced by the quality of services and health facilities. Hospitals must be able to maintain good quality services and health facilities for patients in order to compete with hospitals with better quality services and health facilities. Quality of service is a potential weapon to beat competitors. Health facilities are an important factor in influencing patient satisfaction. Friendly service and good health facilities can increase patient satisfaction resulting in an increase in patient visits. The purpose of this study was to determine or analyze the effect of service quality and health facilities on BPJS patient satisfaction at the hospital. Insani Stabat. This research was conducted at the hospital. Insani Stabat. The type of research used is descriptive quantitative research. The results showed that the variables of service quality and health facilities had an effect either partially or simultaneously on the satisfaction of BPJS patients at the hospital. Insani Stabat. The R Square value of 80.5% indicates that 80.5% of the variable ability of service quality (X1) and health facilities (X2) has an effect on patient satisfaction (Y) at the hospital. Insani Stabat while the remaining 19.5% is the influence of other independent variables that are not explained or not examined by researchers in this study such as location, price and administrative system variables.